PROTOTYPE SMART INSTRUMENT UNTUK KLASIFIKASI PENYAKIT HIPERTENSI BERDASARKAN JNC-7 - Dudi Irawan; Izzati Muhimmah; Tito Yuwono (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
High blood disease or famous to known as hypertension almost 95% the cause is very difficult to know. One way to know the condition of our health is by checking routine to the nearest clinic or hospital. Hypertension is one of the risk factors for dangerous diseases, such as stroke, heart attack, and kidney failure. Hypertension can cause high morbidity (pain) and mortality (death), hypertension is often called silent killer disease. People with Hypertension rarely show early symptoms, and their recognition is usually through screening, or when seeking medical treatment for unrelated health problems. The cause factors of hypertension include weight and height, body fat, and alcohol levels inside of body. To know the condition of body to hypertension need a monitoring system and use tool tensimeter. In this research has been made the means of detecting factor symptoms of hypertension. After the measurements are done by each sensor then the data is processed by Arduino Microcontroller to be processed to computer via serial port (USB). On the computer data that has been sent will be processed using decision tables with databases obtained from experts, the resultin a decision will give classification of hypertension and non-pharmacological management.